Dealing with contaminated Sites from theory towards practical application - Swartjes, Frank A. (Springer Netherlands, 2011)
This standard work on contaminated site management covers the whole chain of steps involved in contaminated site management, from sampling to remediation. An important focus throughout the book has been on Risk Assessment. In addition, the book will include in-depth theories on soil contamination, along with offering possibilities for practical applications. More than sixty of the world?s top experts from Europe, the USA, Australia and Canada have contributed to this book. The twenty-five chapters in this book offer relevant information for experienced scientists, students, consultants and regulators, as well as for "new players" in contaminated site management.